2013
DOI: 10.2174/15680266113136660182
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Cancer Vaccines in the Current NSCLC Clinical Scenario

Abstract: This review is aimed to focus on NSCLC as an emerging and promising model for active immunotherapy and the challenges for its inclusion in the current clinical scenario. Cancer vaccines for NSCLC have been focused as a therapeutic option based on the identification of a tumor hallmark and the active immunization with the related molecules that triggers cellular and/or humoral responses that consequently destroy or delay the rate of malignant progression. This therapeutic intervention in an established disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…OVs are considered as powerful therapeutic agents as they provide good efficacy, fewer side effects, and are less harmful to cancer patients. Currently, several viruses, including vaccinia virus, coxsackievirus, adenovirus, reovirus, herpes simplex virus, measles virus, and maraba virus, are being investigated for use in the treatment of different types of advanced cancers [18,19,51].…”
Section: Vaccinia Virusmentioning
confidence: 99%
See 3 more Smart Citations
“…OVs are considered as powerful therapeutic agents as they provide good efficacy, fewer side effects, and are less harmful to cancer patients. Currently, several viruses, including vaccinia virus, coxsackievirus, adenovirus, reovirus, herpes simplex virus, measles virus, and maraba virus, are being investigated for use in the treatment of different types of advanced cancers [18,19,51].…”
Section: Vaccinia Virusmentioning
confidence: 99%
“…Oncolytic VV has been intensively investigated in many preclinical and clinical studies and has shown promising results [73,74]. The therapeutic efficacy of VV can be further enhanced via genetic engineering by replacing the vTk or VGF gene with targeted therapeutic genes or via the combination with different cancer therapies, such as chemotherapy or radiotherapy [19,61]. In our previous study, we designed a novel oncolytic virus (NOV) by substituting both the vTk and VGF regions with TRAIL and Ang1, respectively, in the VV Wyeth strain genome.…”
Section: Vaccinia Virus For Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer vaccine combinations with chemotherapy face challenges in the clinical application of treatment. Factors such as immunosuppressive tumor microenvironment, advanced age, or disease stage can significantly affect patient outcomes [ 83 ]. Personalized combinations based on predictors of responses and tumor molecular phenotypes may aid in generating better responses and overcome some of the general challenges associated with the combination of cancer vaccines with chemotherapies [ 83 ].…”
Section: Combination Of Cancer Vaccines With Chemotherapymentioning
confidence: 99%